90.4k views
4 votes
Which choice is equivalent to the expression below when x is greater than or equal to 0?

Which choice is equivalent to the expression below when x is greater than or equal-example-1

2 Answers

3 votes

Answer:

Choice A is the correct answer

Explanation:


2x√(2x)

Find the attachment below for the explanation

User Simurg
by
5.2k points
4 votes

For this case we must indicate an expression equivalent to:


\sqrt {18x ^ 3} - \sqrt {9x ^ 3} +3 \sqrt {x ^ 3} - \sqrt {2x ^ 3}

So, rewriting the terms within the roots we have:


18x ^ 3 = (3x) ^ 2 * (2x)\\9x ^ 3 = (3x) ^ 2 * (x)\\x ^ 3 = x ^ 2 * x\\2x ^ 3 = (2x) * x ^ 2

So:


\sqrt {(3x) ^ 2 * (2x)} - \sqrt {(3x) ^ 2 * (x)} + 3 \sqrt {x ^ 2 * x} - \sqrt {(2x) * x ^ 2} =

Removing the terms of the radical:


3x \sqrt {2x} -3x \sqrt {x} + 3x \sqrt {x} -x \sqrt {2x} =

We simplify adding terms:


3x \sqrt {2x} -x \sqrt {2x} -3x \sqrt {x} + 3x \sqrt {x} =\\2x \sqrt {2x} + 0 =\\2x \sqrt {2x}

Answer:

Option A

User Isabelle
by
4.9k points